Implementation of Evidence-Based Research Project-Based Learning in Chemistry Practicum to Improve Students' Conceptual and Argumentation Skills - Salsabila Dia Syahputri; Nadia; Kiki Putri Septya Pratama; Zyahdatul Husna Herlianti; Usman; Wirhanuddin (Orbital: Jurnal Pendidikan Kimia, 2025)
This study is motivated by the importance of improving students’ conceptual understanding and scientific argumentation skills in chemistry practicum, particularly on the topic of acids and bases. It aims to evaluate the effectiveness of the Project-Based Learning (PjBL) model combined with the Evidence-Based Research (EBR) approach in supporting both aspects. This study employs a descriptive quantitative approach using a pre-experimental one-group pretest–posttest design The research subjects were 26 Chemistry Education students who participated in two cycles of practicum. Data were collected through a conceptual understanding test and report analysis using the Toulmin Argumentation Pattern (TAP) rubric, then analyzed descriptively. The results showed an increase in the average conceptual understanding score from 11.81 to 13.15, and the TAP score from 10.46 to 14.15. Most students demonstrated positive development in both aspects. These findings indicate that the PjBL–EBR model is effective in fostering scientific thinking, constructing data-based arguments, and engaging actively during the practicum. The implementation of this model is relevant for exploration-based practicums and is recommended for other chemistry topics. These findings indicate that the PjBL–EBR model is effective in encouraging students to think scientifically, construct evidence-based arguments, and actively engage during practicum activities. This model is considered relevant for exploratory-based practicums and has the potential to be applied to other chemistry topics.